Desenvolvimento de método para determinação de impurezas elementares em medicamentos de acordo com os capítulos USP <232> e USP <233> - Igor Forattini Prates Carvalhais Noronha (2023)
After USP 232 and USP 233 publishing on the United States Pharmacopeia, new challenges have arisen in terms of elemental determination in pharmaceutical products. New limits were stablished for 24 elements, according to toxicity levels. In this context, efficient sample pretreatment methods applied with sensitive and selective instrumental analysis have become a trend in this research line. As so, a new method was developed using ultrasound assisted microextraction. To begin with it, a microwave assisted digestion using diluted nitric acid was validated, with recoveries ranging between 95 e 120% (except Ag and Pd) and RSD < 20% (except Pd). This method was applied to analyze multivitamin pills and the results were used as a reference to optimize the microextraction method, which was optimized according to the acid mixture used for extraction. Two mixtures were efficient: MIX 1 – diluted nitric acid; MIX 3 – nitric acid with hydrofluoridric acid (9:1). Both mixtures were validated according to Chapter USP 233 with recoveries varying between 85 and 120% (except Ag and Pd), RSD < 15% and limits of detection below the maximum permitted concentration for a 10 g day-1 dose drug. The MIX 3 validated method was then applied to analyze 37 samples of antidepressant obtained from local drug stores (with prescription) and federal police donation. Significant levels of Cd, Pb, As, Co, V, Ni, Pd, Ba, Cu, Sn and Cr were detected, but all of them were below the stablished limits.